Organ Donation After Euthanasia: A Dutch Practical Manual. Issue 7 (10th March 2016) - Bollen, J.; de Jongh, W.; Hagenaars, J.; van Dijk, G.; ten Hoopen, R.; Ysebaert, D.; Ijzermans, J.; van Heurn, E.; van Mook, W.
Abstract : Many physicians and patients do not realize that it is legally and medically possible to donate organs after euthanasia. The combination of euthanasia and organ donation is not a common practice, often limited by the patient's underlying pathology, but nevertheless has been performed >40 times in Belgium and the Netherlands since 2005. In anticipation of patients' requests for organ donation after euthanasia and contributing to awareness of the possibility of this combination among general practitioners and medical specialists, the Maastricht University Medical Center and the Erasmus University Medical Center Rotterdam have developed a multidisciplinary practical manual in which the organizational steps regarding this combined procedure are described and explained. This practical manual lists the various criteria to fulfill and the rules and regulations the different stakeholders involved need to comply with to meet all due diligence requirements. Although an ethicist was involved in writing this paper, this report is not specifically meant to comprehensively address the ethical issues surrounding the topic. This paper is focused on the operational aspects of the protocol. Abstract : After carefully reflecting on ethical and logistic considerations, the authors argue that organ donation after euthanasia is feasible.